Effect of Stress-WIN, a novel polyherbal formulation, on DOCA-salt-induced hypertensive Wistar rats - Amit Ranjan; Anirban Roy; Poonam Pal; Somesh Agarwal; Amaresh Kumar Singh; Vinod Tiwari; Shreyans Kumar Jain; Hitesh Harsukhbhai Chandpa; Ankita Yadav; Sanjeev Kumar (Discover Applied Sciences)
Abstract Hypertension is a multifactorial disorder and one of the most important risk factors and a leading cause of stroke, heart disease, and end-organ damage. Hypertension leads to the production of high levels of pro-inflammatory cytokines and cholesterol, which increase thrombogenesis and fibrosis, ultimately resulting in chronic inflammation. Chronic inflammation causes endothelial dysfunction by producing excess reactive oxygen species (ROS) through pro-inflammatory cytokines such as interleukine-1β (IL-1β) and tumor necrosis factor-α (TNF-α). Further, the high level of nitric oxide (NO) and malonaldehyde (MDA) increases the oxidative stress, which worsens the liver's production of SGOT and SGPT and glomerular filtration of the kidney. In this study, an Ayurvedic polyherbal formulation (StressWIN) was shown to be a potent therapeutic drug for the treatment of deoxycorticosterone (DOCA)-salt-induced hypertension in Wistar rats. This study showed that administration of Stress-WIN significantly reduced the expression of pro-inflammatory cytokines (IL-1β and TNF-α) and also reduced the level of ROS, NO, MDA, SGOT, and SGPT in the serum of DOCA-salt-induced hypertension in Wistar rats. Furthermore, Stress-WIN treatment exhibited reduced cholesterol levels and glutathione concentration. Histological analysis showed that infiltration of immune cells was reversed by Stress-WIN A treatment (500 mg/kg and 1000 mg/kg). Furthermore, Stress-WIN A (2000 mg/kg) administration attenuated DOCA-salt-mediated morphological changes in the kidney and the heart of the Wistar rat. These promising outcomes underscore the potential of Stress-WIN as a viable alternative or adjunct therapy for hypertension, warranting further clinical investigations.